Mediação de leitura literária em redes sociais e a formação do leitor - Letícia Gantzias Abreu (2023)
This research is contextualized in the area of Applied Linguistics and its general objective is to map the reading skills noticeable in reviews shared by three virtual reading mediation groups: Bookstagrammers (Instagram), Booktubers (YouTube) and Booktokers (Tiktok), and verify the potential of this type of measurement in the development of reading skills in high school students. To this end, we use as theoretical support studies that address the themes of reading practice and mediation, reading skills, mediation of literary reading in the digital era and digital technologies in human life, focusing on authors such as Ceccantini (2009), Colomer (2007 ), Larrosa (2014), Petit (2019), Gibson (1979/1986), Kress (2010) and Rojo (2019), among others, in addition to data from the International Student Assessment Program (PISA), 2018 edition, of National Common Curricular Base (BNCC, 2018), data from the Portraits of Reading in Brazil (2021) survey and the O Brasil que Lei (2021) survey. In addition to the bibliographical survey, the thesis is structured in two moments: a mapping and a practical application. Initially, the mapping, made through inferences, shows the reading skills shared in literary reviews on three social networks (Youtube, Instagram and TikTok); Next, we sought to verify the demonstration of reading skills shared in literary reviews produced by primary school students, through a practical application carried out in a school. Therefore, to analyze this data, based on the theoretical foundation, we developed parameters that can serve as a parameter for future investigations. The results show that the demonstration of reading skills on social networks can vary due to some factors that act as conditioning factors: 1- The conception of the textual genre 2- The reading skills mastered (or developed) (Locate, Understand, Evaluate and Reflect ); 3- The style of the review producer; 4- The social network (YouTube, Instagram or Tiktok) used. We hope that the thesis contributes by offering more opportunities for multiliteracy at school, as it presents a new didactic possibility with the insertion of virtual literary communities.